1976
DOI: 10.1056/nejm197608192950803
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Aspects of Theophylline in Premature Newborns

Abstract: To characterize further the pharmacokinetics of theophylline in premature infants, its concentraion in blood was measured by high-pressure liquid chromatography after intravenous infusion given to six apneic premature newborns three to 15 days of age. Theophylline's apparent volume of distribution was 0.690 +/- 0.095 liters per kilogram (mean +/- S.E.), a value similar to that of children, but the half-life (30.2 +/- 6.5 hours) was nine times longer. Blood clearance rate (17.6 +/- 2.3 ml per kilogram per hour)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
4
4

Year Published

1978
1978
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(84 citation statements)
references
References 18 publications
7
69
4
4
Order By: Relevance
“…Kadlec et al (1978) found a mean half-life of 4.9 h for theophylline elimination in a population of 54 children who were between three months and six years old and were given the compound orally. The half-life was much longer, 30 h, in six premature newborn children 3 to 15 days old (Aranda et al, 1976). The main pathway of theophylline metabolism in adult humans agrees fairly well with the pathway of caffeine metabolism.…”
Section: Metabolism In the Adult Human Beingsupporting
confidence: 64%
“…Kadlec et al (1978) found a mean half-life of 4.9 h for theophylline elimination in a population of 54 children who were between three months and six years old and were given the compound orally. The half-life was much longer, 30 h, in six premature newborn children 3 to 15 days old (Aranda et al, 1976). The main pathway of theophylline metabolism in adult humans agrees fairly well with the pathway of caffeine metabolism.…”
Section: Metabolism In the Adult Human Beingsupporting
confidence: 64%
“…This probably reflects the large variability in volume of distribution reported in neonates and differences between studies in gestational and postnatal age of the participants. 14,17,18 In a small study, Lagercrantz et al 16 found that the optimal effect of theophylline for apnea of prematurity was achieved when its plasma concentration was at least 7.25 g/ml. Also, Muttitt et al reported more than 50% clinical response to theophylline only when a level of about 12.7 g/ml was achieved, although the likelihood of side effects such as tachycardia is much higher above those concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of binding in HSA was very similar to that of plasma at equivalent albumin con0o. al., 1974; Aranda et al, 1976;Piafsky et al, 1977) although not with that of Simons et al (1978) or Mangione et al (1978) who indicated that the percentage unbound might vary by 50 to 100% even in healthy individuals. The reason for such discrepancies is unclear but may also relate to methodological differences.…”
Section: The Effect Ofproteinsmentioning
confidence: 96%